Electrospun polylactic acid-chitosan composite: a bio-based alternative for inorganic composites for advanced application - Thomas, Merin Sara; Pillai, Prasanth K. S.; Faria, Marisa; Cordeiro, Nereida; Barud, Hernane [UNESP]; Thomas, Sabu; Pothen, Laly A. (Springer Nature, 2018)
Fabricating novel materials for biomedical applications mostly require the use of biodegradable materials. In this work biodegradable materials like polylactic acid (PLA) and chitosan (CHS) were used for designing electrospun mats. This work reports the physical and chemical characterization of the PLA–CHS composite, prepared by the electrospinning technique using a mixed solvent system. The addition of chitosan into PLA, offered decrease in fiber diameter in the composites with uniformity in the distribution of fibers with an optimum at 0.4wt% CHS. The fiber formation and the reduction in fiber diameter were confirmed by the SEM micrograph. The inverse gas chromatography and contact angle measurements supported the increase of hydrophobicity of the composite membrane with increase of filler concentration. The weak interaction between PLA and chitosan was confirmed by Fourier transform infrared spectroscopy and thermal analysis. The stability of the composite was established by zeta potential measurements. Cytotoxicity studies of the membranes were also carried out and found that up to 0.6% CHS the composite material was noncytotoxic. The current findings are very important for the design and development of new materials based on polylactic acid-chitosan composites for environmental and biomedical applications. [Figure not available: see fulltext.].